Use of Devops in Very Small Entities: Systematic Mapping - Acevedo-Duenas, Daniela; Munoz, Mirna; Galvan-Cruz, Sergio (2023 12th International Conference On Software Process Improvement (CIMPS), 2023)
This paper presents a systematic mapping of DevOps in Vey Small Entities (VSE). DevOps is an approach that combines software development and technological operations to improve efficiency and speed in the delivery of applications and services. As a result, 18 primary studies addressed tools, implementation in very small entities, and commonly automated activities in the DevOps process. Besides, this study focuses on the challenges and opportunities in DevOps, highlighting the importance of selecting appropriate tools and architectures and the need for implementation guides for very small entities.